2020
DOI: 10.3390/mi11060545
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate Effect on the Ductile Brittle Transition in Grinding Hot Pressed SiC Ceramics

Abstract: Surface and subsurface damage are still persistent technical challenges for the abrasive machining hot pressed-silicon carbide (HP-SiC) ceramics. Therefore, an investigation of the material behavior and critical depth of ductile to brittle transition (DBT) is essential for improving high precision and quality grinding HP-SiC ceramics. In this paper, single-grit grinding experiments with different scratch speed were conducted to study strain rate effect on the critical depth of DBT. The nanoindentations were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Or does the material respond differently to these two type of loadings? A few researchers for example: Kovelchenko et al [5], Pratap et al [6] and Huang et al [7], have reported INCD-DECD scratching of silicon, with distinct research hypothesis, and there are clear indications that there is an effect of manner of scratching (INCD or DECD) on the deformation behavior but the reasons for this have not been explored. An investigation similar to indentation studies, where in the force-depth graph is compared during loading and unloading conditions, needs to be performed for increasing and decreasing depth scratches.…”
Section: Introductionmentioning
confidence: 99%
“…Or does the material respond differently to these two type of loadings? A few researchers for example: Kovelchenko et al [5], Pratap et al [6] and Huang et al [7], have reported INCD-DECD scratching of silicon, with distinct research hypothesis, and there are clear indications that there is an effect of manner of scratching (INCD or DECD) on the deformation behavior but the reasons for this have not been explored. An investigation similar to indentation studies, where in the force-depth graph is compared during loading and unloading conditions, needs to be performed for increasing and decreasing depth scratches.…”
Section: Introductionmentioning
confidence: 99%